PENGARUH CUSTOMER RELATIONSHIP MARKETING DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN - Widya Syaraswati; Satiti Handini (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to determine and examine the effect of Customer Relationship Marketing and Service Quality on Customer Satisfaction. Samples were taken as many as 100 respondents using purposive sampling technique. The research data analysis method uses multiple linear regression analysis with the help of SPSS software applications. The results showed that the variables of Customer Relationship Marketing and Service Quality had a significant effect on customer satisfaction